2020
DOI: 10.1055/s-0040-1716672
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Utilization in Patients Undergoing Repeat Stereotactic Radiosurgery for Vestibular Schwannoma with 5-Year Follow-up: A National Database Analysis

Abstract: Background Stereotactic radiosurgery (SRS) has been used as an alternative to microsurgery in patients with small vestibular schwannoma (VS). We compare health care utilization metrics in patients undergoing repeat-SRS (re-SRS) and no repeat SRS (nr-SRS) at long-term follow-up. Materials and Methods We queried the MarketScan database using International Classification of Diseases, Ninth Revision and Current Procedural Terminology 4, from 2000 to 2016. We included adult patients who had diagnosis of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In our study, we found that median combined payments for the s-PSM cohort were $74,683 and $83,351 compared to $42,664 and $63,942 for ns-PSM and $9,476 and $ 18,839 for the nd-PSM cohort, respectively, at one-and two-years following VS surgery. In our previous study, we reported that the combined median payments for patients who underwent stereotactic radiosurgery (SRS) for VS were $8,751 and $18,266 at oneand two-years, respectively [19]. Also, patients who underwent repeat SRS received median payments of $28,418 and $49,068 at one-and two-years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that median combined payments for the s-PSM cohort were $74,683 and $83,351 compared to $42,664 and $63,942 for ns-PSM and $9,476 and $ 18,839 for the nd-PSM cohort, respectively, at one-and two-years following VS surgery. In our previous study, we reported that the combined median payments for patients who underwent stereotactic radiosurgery (SRS) for VS were $8,751 and $18,266 at oneand two-years, respectively [19]. Also, patients who underwent repeat SRS received median payments of $28,418 and $49,068 at one-and two-years, respectively.…”
Section: Discussionmentioning
confidence: 99%